Pelayanan One Stop Service (OSS) dalam Pengurusan Perizinan Investasi pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) di Kabupaten Majalengka - Rhidan Muhammad Khaidar; Turtiantoro . (Journal of Politic and Government Studies, 2020)
One Stop Service (OSS) is one of the governments policy to give amenity ifservice to public. The purpose of one stop service in investment licensing is toprovide convenience for the public, particularly for the entrepreneurs or investorsto obtaining a business licence which is expected to be able to interest theenthusiasm of investors. One stop service in every regency is applied bt one stopservice agency. Majalengka is one if regency which one stop service withDPMPTSP of Majalengka Regency as executor.One stop service is the activity of licensing and non-licensing which itsmanagement process starts from the application stage until the document ispublished in one place. In One Stop Service, the head of the PTSP is delegated theauthority to sign the entry permit, this means simplifying the services.Simplification of service is an effort to increase the time, procedure, and cost oflicensing and non licensing. Licensing is the granting of legality to a certainperson or business actor/activity, either in the form of a license or a sign of business list. One Stop Service (PTSP) is expected to cut the time and cost neened to manage licensing. The purpose of this study is to evaluate the achievement of the objectives of One Stop Service licensing system at the DPMPTSP of Majalengka Regency. The research method used is descriptive research type with qualitative approach. This study also obtained from interviews, observations, and reindorced with documentation in accordance with the focus of the problem of One Stop Service (OSS) at the investment, the research is located in Majalengka regency, while the research site is at the DPMPTSP in Majalengka regency. Based on the results of research and discussion, it can be concluded ; First, One Stop Service policy towards investment in Majalengka Regency born to provide service in the field of licensing with the motto CERIA (Fast, Effectif, Responsif, Inovatif and Credible) through one door (One Stop Service) second. The resources in system one stop service at the investment and licensing agency of Majalengka Regency has been well, include human resource, facility resource, and authority signing licensing. Third, Disposition of staff in system one stop service is be well. Fourth, The evaluation results in system one stop service policy in Majalengka, although the benefits are already keenly felt, but there are still some problems faced. Fifth, as an effort Majalengka Regency Local Government to address these issues, is necessary to formulate strategic policies to realize the ideal model of the future policy of One Stop Service which according to the times.Keywords: Public Service, One Stop Service, Investment Licensing